Between Scylla and Charybdis: Charting an Ethical Course for Research Into Financial Incentives for Living Kidney Donation. Issue 5 (31st March 2015) - Fisher, J. S.; Butt, Z.; Friedewald, J.; Fry‐Revere, S.; Hanneman, J.; Henderson, M. L.; Ladin, K.; Mysel, H.; Preczewski, L.; Sherman, L. A.; Thiessen, C.; Gordon, E. J.
Abstract : New approaches to address the kidney scarcity in the United States are urgently needed. The greatest potential source of kidneys is from living donors. Proposals to offer financial incentives to increase living kidney donation rates remain highly controversial. Despite repeated calls for a pilot study to assess the impact of financial compensation on living kidney donation rates, many fear that financial incentives will exploit vulnerable individuals and cast the field of transplantation in a negative public light, ultimately reducing donation rates. This paper provides an ethical justification for conducting a pilot study of a federally regulated approach to providing financial incentives to living kidney donors, with the goal of assessing donors' perceptions. Abstract : This paper provides an ethical justification for conducting a pilot study of a federally regulated approach to providing financial incentives to living kidney donors, with the goal of assessing donors' perceptions. Also see viewpoint by Delmonico et al (page1187 ) and meeting report by Salomon et al (page1173 ).